Evaluation of urban water security based on DPSIR model. Issue 1 (October 2021) - Shi, Sha; Tao, Xueting; Chen, Xiaona; Chen, Hao; Fitri, Arniza; Yang, Xiaojia
Abstract: Assessment of urban water security is an important scientific basis for the sustainable utilization of urban water resources. This study established an evaluation model for urban water security based on DPSIR model, entropy method and comprehensive index method. The model was applied to Gong Qingcheng City (GQCC) in Jiangxi Province, China. An indicator system is developed based on four aspects including social development, water resources status, water pollution and water resources management, as well as summing up predecessors' experience. This study analysed per capita domestic water consumption; ratio of ecological water compensation; percentage of water conservancy and public infrastructure investment; and water consumption per ten thousand yuan of industrial output value; where ratio of urban sewage treatment are the main effects on urban water security. The results of single index evaluation show that the change of stress subsystem was most dramatic from 2013 to 2017, while others were relatively stable. This indicates that positive interventions were urgently needed to relieve pressure of the stress subsystem. The results of comprehensive index evaluation show that water security at GQCC was in a critical state. In this paper, the causal relationship between social development and water security was clarified while the main factors and other factors affecting urban water security was identified. Finally, a reference for the formulation of urban development planning based on water resources demand was provided.